2020
DOI: 10.1016/j.patrec.2019.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Selective feature connection mechanism: Concatenating multi-layer CNN features with a feature selector

Abstract: Different layers of deep convolutional neural networks(CNNs) can encode different-level information. Highlayer features always contain more semantic information, and low-layer features contain more detail information. However, low-layer features suffer from the background clutter and semantic ambiguity. During visual recognition, the feature combination of the low-layer and high-level features plays an important role in context modulation. If directly combining the high-layer and low-layer features, the backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Compared with the performance between the trainings without pre-trained weights and with pre-trained COCO weights, transfer learning could save training time without compromising detection performance. The latter training only involved the heads of FPN, RPN and detection branches, containing high-level semantics [ 36 ]. Such semantics may be more important for instance segmentation and object detection than low-level generic features extracted by the bottom architecture of the detectors [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the performance between the trainings without pre-trained weights and with pre-trained COCO weights, transfer learning could save training time without compromising detection performance. The latter training only involved the heads of FPN, RPN and detection branches, containing high-level semantics [ 36 ]. Such semantics may be more important for instance segmentation and object detection than low-level generic features extracted by the bottom architecture of the detectors [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…If connecting the high-level convolutional features and low-level convolutional features, we will obtain richer and more discriminative convolutional features for vein recognition. However, the study [45] indicated that directly connecting the high-level convolutional features and low-level convolutional features as images representation cannot obtain the excellent result due to the fact that low-level convolutional contain some background information.…”
Section: A the Analysis Of Convolutional Features With Vein Informationmentioning
confidence: 99%
“…It is equally important to mention that many promising methods based on multimodel/multimodal deep learning have been applied to image classification [21][22][23][24][25][26][27]. ere are two commonly multimodel strategies: feature fusion and ensembles of multiple classifiers.…”
Section: Computational Intelligence and Neurosciencementioning
confidence: 99%
“…However, it can lead to "the curse of dimensionality" problem and does not guarantee the optimal accuracy due to the difference of feature ranges. Otherwise, combining high-level information with low-level information features can introduce the background clutter and semantic ambiguity due to the appearance of artifacts [24]. In the ensembles of multiple classifiers, each single classifier independently performs its task.…”
Section: Computational Intelligence and Neurosciencementioning
confidence: 99%